2001
DOI: 10.1163/156853801750096150
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and survival rate of waterfrog tadpoles in relation to biotic and abiotic factors: a field experiment

Abstract: Abstract. Predictions about population and community dynamics are usually based on lab experiments. Because the results are dif cult to transfer to natural conditions, the major purpose of this study was to test the effects of biotic and abiotic factors on tadpole populations in a natural environment . We stocked six ponds, created the previous year, with known numbers of Rana esculenta and R. lessonae tadpoles and followed their developmen t over several months. When compared among ponds, tadpole density corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The tendency for large body size in ponds with many predators is opposite from the induced response in most predation experiments (Lardner 2000, Van Buskirk 2000. However, a similar pattern has been noted in other field studies and may be caused by higher productivity or otherwise improved conditions in ponds with more predators (Thurnheer and Reyer 2001). This interpretation is supported by observations of a positive correlation between densities of amphibian larvae and their predators, suggesting that both groups of animals may respond to underlying variation in the quality of the environment (Van Buskirk 2005).…”
Section: Relationships Between Morphology and Habitat Gradientssupporting
confidence: 67%
“…The tendency for large body size in ponds with many predators is opposite from the induced response in most predation experiments (Lardner 2000, Van Buskirk 2000. However, a similar pattern has been noted in other field studies and may be caused by higher productivity or otherwise improved conditions in ponds with more predators (Thurnheer and Reyer 2001). This interpretation is supported by observations of a positive correlation between densities of amphibian larvae and their predators, suggesting that both groups of animals may respond to underlying variation in the quality of the environment (Van Buskirk 2005).…”
Section: Relationships Between Morphology and Habitat Gradientssupporting
confidence: 67%
“…Tadpoles of three species of frogs in central Brazil use the shallower parts of a pond for all or part of the year (Barreto and Moreira 1996). Rana esculenta and R. lessonae tadpoles also use shallower portions of ponds (Thurnheer and Reyer 2001). found that the use of shallower parts of a pond by bullfrog tadpoles (Rana catesbeiana) was influenced by season; deeper water was used during the summer and shallower water in the winter.…”
Section: Downloaded By [State University Ny Binghamton] At 07:27 18 Nmentioning
confidence: 98%
“…The frogs were transferred to two fenced-artificial ponds near Zü rich. The ponds were 60 cm deep, with a surface area of 40 m 2 , and were surrounded by fine-meshed steel fences similar to those used in the terrestrial experiment (for details, see Thurnheer and Reyer 2001). On 15 May and 22 June 2000, we recaptured the surviving frogs, identified, weighed, and measured them.…”
Section: Monitoring Survival and Growth In The Terrestrial Habitatmentioning
confidence: 99%